PENGEMBANGAN BUKU DIGITAL KIMIA PADA MATERI TITRASI ASAM BASA BERBASIS INKUIRI - Priyatni, Petri; Rusdi, M; Effendi-Hasibuan, Muhammad Haris (Jurnal Pendidikan Kimia Universitas Riau, 2020)
Analysis of the needs of teachers and students states that learning required teaching materials that utilized multimedia as a learning medium that could be accessed on cellphones (laptops) and laptops. This study is aimed to develop learning media in the form of inquiry-based digital chemistry books on acid-base titration material. This type of research is a research and development study using the ADDIE model. The subjects in this study were chemistry teachers and students of class XI Mipa 1 in SMA Plus N 2 Banyuasin III. The instruments used to collect data were in the form of questionnaires, interviews, and daily logs. From the results of media validation, material validation and learning design validation state that this digital chemistry book is suitable for use in acid-base titration material. The results of the assessment of two chemistry teachers on digital books were stated to be very good with the kappa test obtained a value of 0.814. In the one-on-one trial, it was 86.67% feasibility, and in the small-group trial it was 95%. Chemistry digital books on inquiry- based acid-base titration material are appropriate for use in chemistry learning and are expected to be applied in learning to improve studentsÂ critical thinking skills.